Principles of the institutional law of international organizations - Amerasinghe, Chittharanjan Felix, 1933- (Cambridge University Press, 2005)
The second edition of C.F. Amerasinghe's successful book, which covers the institutional aspects of the law of international organizations, has been revised to include, among other things, a new chapter on judicial organs of international organizations, as well as a considerably developed chapter on dispute settlement. There is a rigorous analysis of all the material alongside a functional examination of the law. A brief history of international organizations is followed by chapters on, amongst others, interpretation, membership and representation, international and national personality, judicial organs, the doctrine of ultra vires, liability of members to third parties, employment relations, dissolution and succession, and amendment. Important principles are extracted and discussed, and the practice of different organizations examined.
Previous edition: 1996.
Keywords: International agencies.; International law.; Organisations internationales.; international organizations.; LAW -- International.; International agencies; International law